2022
DOI: 10.1039/d2cp00643j
|View full text |Cite
|
Sign up to set email alerts
|

Emulating proton transfer reactions in the pseudo-protic ionic liquid 1-methylimidazolium acetate

Abstract: Proton transfer reactions can enhance conductivity in protic ionic liquids. However, several proton reactions are possible in a multicomponent system of charged and neutral species, resulting in a complex reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…Our simulation still reproduces the equilibrium value of 30% ionic:70% neutral molecules (Jacobi et al, 2022;Joerg and Schröder, 2022) for both s-values as shown in Figure 8.…”
Section: Beforesupporting
confidence: 66%
See 4 more Smart Citations
“…Our simulation still reproduces the equilibrium value of 30% ionic:70% neutral molecules (Jacobi et al, 2022;Joerg and Schröder, 2022) for both s-values as shown in Figure 8.…”
Section: Beforesupporting
confidence: 66%
“…4 to prohibit drifting away from the equilibrium partitioning of the molecules as the total number of proton transfer events, i.e. 5,000, is much lower than in the Markov chain analysis reported by Jacobi et al (2022). Furthermore, due to the distance criterion r max and the mutual orientation of the reacting species in the liquid phase, particular reactions are favored regardless of the value of the reaction probability p ref .…”
Section: Beforementioning
confidence: 92%
See 3 more Smart Citations